Kajian Kebijakan Pemberian Insentif Pajak dalam Mengatasi Dampak Virus Corona di Indonesia Tahun 2019 - Selvi Selvi; Alief Ramdhan (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to examine the provision of tax incentives in Indonesia which is being hit by a corona virus outbreak. This research is a literature study. The results showed that the tax incentives provided by the government were conceptually quite good, although there were a number of notes from researchers regarding losses due to a decrease in tax revenue as an implication of the reduction and tax exemption provided by the government. In addition, it is best to exempt income tax on imports, which needs to be reviewed, especially regarding the qualifications of goods that can be incentivized. The government also needs to conduct overall supervision to minimize irregularities that are detrimental to many parties.